Acute, dose–response effects of guayusa leaf extract on mood, cognitive and motor-cognitive performance, and blood pressure, heart rate, and ventricular repolarization - Nathaniel J. Helwig; Laura E. Schwager; Alexander C. Berry; Anna C. Zucker; Jacob S. Venenga; Samantha C. Sterbenz; Nathaniel D.M. Jenkins (Journal of the International Society of Sports Nutrition)
An emerging sector of the nootropic market is tea-based nutraceutical products, but there are limited data assessing the dose-dependent effects of these products.Purpose We conducted a randomized, double-blind, placebo-controlled crossover trial in young adults to examine the dose-dependent (600 mg versus 1200 mg), acute effects of consumption of an Ilex guayusa tea extract (GLE) on mood, cognitive and motor-cognitive performance, as well as its acute cardiovascular effects.Methods Twenty-five adults (mean ± SD, age = 28 ± 7 y; 9 M/16 F) completed familiarization and then three randomly ordered experimental visits where they consumed either 600 mg (GLE600) or 1200 mg (GLE1200) GLE or placebo (PLA). Following supplement consumption, participants completed a mood state survey, assessments of perceived jitteriness, energy, and focus, and neurocognitive and motor-cognitive testing. Blood pressure (BP), heart rate, and QT interval length were determined before and after supplementation.Results GLE600 significantly improved total mood disturbance (mean ± SE difference = -6.9 ± 2.6 au, p = 0.034), fatigue-inertia (−2.84 ± 0.89 au, p = 0.008), perceived energy (+13.00 ± 4.49 au; p = 0.02), motor speed (+4.52 ± 1.42 au, p = 0.008), and psychomotor speed (+7.20 ± 2.16 au, p = 0.005) relative to PLA. GLE1200 also improved psychomotor speed (+5.08 ± 2.16 ms, p = 0.045) and uniquely increased motor-cognitive performance as reflected by a decrease in reaction time (−0.106 ± 0.04 ms, p = 0.026) during a neurocognitive hop test. The effect of GLE on jitteriness was both dose- and sex-dependent. Jitteriness increased with increasing GLE dose in women only (p < 0.001). Both GLE600 and GLE1200 similarly increased systolic and diastolic BP by 4–5 mmHg (p ≤ 0.022). Neither GLE600 nor GLE1200 acutely influenced QTc length (p = 0.31).Conclusions The goal of GLE supplementation should be considered when selecting a dosing strategy. Lower dosages of GLE (e.g. 600 mg) appear to optimize cognitive and mood-related outcomes while limiting side-effects such as jitteriness in women, and higher dosages may be necessary (e.g. 1200 mg) to promote improvements in motor-cognitive performance.